(untitled) (Reflection and Critique Law Magazine, 2024)
This article aims to point out the main barriers that hinder the process of criminalization of LGBTphobia. Although, an understanding was signed by the Federal Supreme Court (STF), in 2019, through a Direct Action of Unconstitutionality by Omission and a Mandate of Injunction, equating it to the crime of racism typified by Law n. 7,716/89, it is still notorious that there are obstacles that make it difficult or impossible for victims to have access to their rights, especially by public security authorities and the Judiciary. This time, this research intends to analyze the law of criminalization of LGBTphobia, the most recent report of the research “Discrimination and violence against the LGBTQIA+ population” (2022), of the National Council of Justice (CNJ), as well as a diversity of works that corroborate the theme. Considering the multidisciplinary nature of the subject, the intersection of several branches of law, such as Criminal Law, Constitutional Law, Fundamental Human Rights, among others, will be made. Keywords: LGBTphobia; Criminalization; Preconception.